Cultivating Resilience: A Policy Brief for Adapting Bihar’s Rice-Wheat Systems to Climate Uncertainty - Samaddar, Arindam; Munshi, Sugandha; Srivastava, Amit; Patil, Vikram; Peramaiyan, Panneerselvam; Kumar, Virender (International Rice Research Institute, 2025)
Key Messages for Decision-Makers